Analisis Perubahan Garis Pantai Menggunakan Citra Satelit Landsat 8 dengan Metode Linear Regression Rate di Wilayah Pesisir Kecamatan Kuta - Selpia Purba; Winardi Tjahyo Baskoro; Tomy Gunawan; I Nengah Artawan; I Gusti Agung Putra Adnyana; I Nengah Sandi (Kappa Journal, 2025)
Coastal areas are dynamic environments and are vulnerable to natural processes and human activities, making regular monitoring important for sustainable management. This study analyzes coastal changes along the Kuta coastal area, which includes Pantai Jerman, Kuta, Legian, and Seminyak, using Landsat 8 satellite imagery through the application of the NDWI analysis and the Linear Regression Rate (LRR) method over the period 2014–2022. The NDWI is derived using Band 3 (green) and Band 5 (near-infrared) to accurately classify the boundary between water and land. The LRR method is employed to calculate the trend of coastal line shifts from temporal data, yielding a detailed estimation of the coastal displacement rate. The study results indicate that the Kuta coastal area undergoes changes dominated by mild accretion, with an average coastal shift of 1.50 m/year, while mild erosion occurs at an average of 1.30 m/year. Overall, the coastal area experienced an accretion of 9.52 ha and an erosion of 4.55 ha.